PENERAPAN METODE HYPNOTEACHING MENGEMBANGKAN KOGNITIF ANAK USIA 5-6 TAHUN DI TK BRUDER NUSA INDAH - Olyvia, Marta; Fadillah, Fadillah; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the application of the Hypnoteaching method to develop cognitive skills of 5-6 years old children at TK Bruder Nusa Indah, South Pontianak District, Pontianak City. This study used a qualitative method. The data source of this study was 1 teacher and children of the B3 group of TK Bruder Nusa Indah. This research technique was observation with wide observation tools, direct interview techniques with interview sheets and documentaries with documentation tools. Data analysis in this study was data collection, data reduction, presentation and conclusion/verification based on the results of research that has been done obtained that learning planning used a curriculum made by the teacher. The implementation of learning used the picture media and textbooks to develop the child's cognitive teacher see if the child can understand the command, the child can answer and the child develops the idea. Evaluate the child through question and answer to the child related to the subject of lessons that have been studied together. Children's cognitive development was included in the developing group as expected because from 16 children there are only 3 children who have not yet developed in understanding commands, in answering teacher questions and have not been able to develop their ideas.Key words: Cognitive, HypnoteachingAbstractThis study aimed to determine the application of the Hypnoteaching method to develop cognitive skills of 5-6 years old children at TK Bruder Nusa Indah, South Pontianak District, Pontianak City. This study used a qualitative method. The data source of this study was 1 teacher and children of the B3 group of TK Bruder Nusa Indah. This research technique was observation with wide observation tools, direct interview techniques with interview sheets and documentaries with documentation tools. Data analysis in this study was data collection, data reduction, presentation and conclusion/verification based on the results of research that has been done obtained that learning planning used a curriculum made by the teacher. The implementation of learning used the picture media and textbooks to develop the child's cognitive teacher see if the child can understand the command, the child can answer and the child develops the idea. Evaluate the child through question and answer to the child related to the subject of lessons that have been studied together. Children's cognitive development was included in the developing group as expected because from 16 children there are only 3 children who have not yet developed in understanding commands, in answering teacher questions and have not been able to develop their ideas.Key words: Cognitive, Hypnoteaching